The Role of Civics Teachers in Increasing Interest and Motivation in Learning for Class X MIPA 3 Students at SMA Negeri 16 Bone - Rusdi, Muhammad; Ridha, Rasyid; Ilham, Ilham; Murni, Murni (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study aims to determine the Role of Teachers in Increasing Interest and Motivation to Learn PPKn Students  of Class X MIPA 3 SMA Negeri 16 Bone. The type of research used is qualitative research method. The data processed is the result of interviews with PKN teachers and class X MIPA 3 students. The data collection method used in this study is Observation, Interview and Documentation where the author sees directly the situation in the field. The results of the research obtained by the author are The role of teachers is very important in increasing student interest and motivation to learn, teachers also have several ways to increase the interest and motivation of different students such as in delivering material so that it is easy to understand and create a learning atmosphere.